2018
DOI: 10.1038/s41467-018-05812-2
|View full text |Cite|
|
Sign up to set email alerts
|

SUMOylation of VEGFR2 regulates its intracellular trafficking and pathological angiogenesis

Abstract: Regulation of VEGFR2 represents an important mechanism for the control of angiogenesis. VEGFR2 activity can be regulated by post-translational modifications such as ubiquitination and acetylation. However, whether VEGFR2 can be regulated by SUMOylation has not been investigated. Here we show that endothelial-specific deletion of the SUMO endopeptidase SENP1 reduces pathological angiogenesis and tissue repair during hindlimb ischemia, and VEGF-induced angiogenesis in the cornea, retina, and ear. SENP1-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 52 publications
2
61
1
Order By: Relevance
“…In contrast, higher expression of SUMOylation (protein level) and Wnt/b-catenin, RAP1, and Notch signaling pathways (mRNA level) were observed in VEGF immune desert tumors and corresponded to the highest endothelial cell signature (t test adjusted p < 0.05) ( Figures 6B and S6E). The differential expression of VEGFR1 (FLT1) (t test adjusted p < 0.05) and multiple angiogenic-related signaling pathways may be representative of distinct mechanisms of endothelial cell recruitment and tumor vasculature formation between the two subtypes (Birdsey et al, 2015;Cao, 2013;Chrzanowska-Wodnicka, 2013;Hellströ m et al, 2007;Zhou et al, 2018;Zhu et al, 2017 Table S7). Previous reports have established a relationship between HIF-2a and MYC-induced transcription in renal carcinomas (Gordan et al, 2007a(Gordan et al, , 2008, with MYC regulation of metabolism functioning in concert with and independent of HIF-1 signaling (Gordan et al, 2007b).…”
Section: Characterization Of Immune Infiltration In Ccrccmentioning
confidence: 99%
“…In contrast, higher expression of SUMOylation (protein level) and Wnt/b-catenin, RAP1, and Notch signaling pathways (mRNA level) were observed in VEGF immune desert tumors and corresponded to the highest endothelial cell signature (t test adjusted p < 0.05) ( Figures 6B and S6E). The differential expression of VEGFR1 (FLT1) (t test adjusted p < 0.05) and multiple angiogenic-related signaling pathways may be representative of distinct mechanisms of endothelial cell recruitment and tumor vasculature formation between the two subtypes (Birdsey et al, 2015;Cao, 2013;Chrzanowska-Wodnicka, 2013;Hellströ m et al, 2007;Zhou et al, 2018;Zhu et al, 2017 Table S7). Previous reports have established a relationship between HIF-2a and MYC-induced transcription in renal carcinomas (Gordan et al, 2007a(Gordan et al, , 2008, with MYC regulation of metabolism functioning in concert with and independent of HIF-1 signaling (Gordan et al, 2007b).…”
Section: Characterization Of Immune Infiltration In Ccrccmentioning
confidence: 99%
“…All together, these data indicate that SUMOylation inhibits VEGFR2-dependent angiogenesis ( Fig. 18.2), suggesting that the balance between the SUMOylated and non-SUMOylated VEGFR2 dictates its activation during angiogenesis (Zhou et al, 2018).…”
Section: The Regulation Of Vegfr By Ubiquitination and Sumoylationmentioning
confidence: 70%
“…Based on the studies summarized here, it is clear that ubiquitination plays a major role in the regulation of VEGFR signalling and trafficking in angiogenesis. Interestingly, a study using a knock out mouse model of the de-SUMOylase SENP1 has described that also SUMOylation regulates the intracellular trafficking of VEGFR (Zhou et al, 2018). In particular, it has been demonstrated that SENP1 protein levels increase in vascular endothelial cells in response to ischaemia.…”
Section: The Regulation Of Vegfr By Ubiquitination and Sumoylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, sumoylation may also influence downstream targets of the HIF axis like the VEGF-dependent responses. The VEGF-induced angiogenic response was inhibited by SENP1 silencing, mainly because of VEGFR2 sumoylation and its subsequent accumulation at the Golgi apparatus [148]. Interestingly, products of HIF-1 gene targets, such as glucose transporters GLUT4 and GLUT1, also interact with Ubc9 and can be conjugated to SUMO [149,150].…”
Section: Sumoylation Of Targets That Indirectly Affect the Hypoxic Pamentioning
confidence: 99%